Respuesta :

Answer:

x = -3 + i√6 and x = -3 - i√6

Step-by-step explanation:

Let's apply the "completing the square" method to find the roots of this equation.

Take half of the coefficient 6 of x, square it and add this result to x^2 + 6x.  Then subtract the same quantity:

x^2 + 6x + 15 becomes

x^2 + 6x + 3^2 - 3^2 + 15 = 0

Rewriting the first three terms as the square of a binomial, we ge:

(x + 3)^2 - 9 + 15 = 0, which simplifies to:

(x + 3)^2 + 6 = 0, or (x + 3)^2 = -6

Taking the square root of both sides:

x + 3 = ±i√6

Then the two roots are complex:

x = -3 + i√6 and x = -3 - i√6

ACCESS MORE